Infantile Seborrheic Dermatitis - Pandita, Aakash; Sharma, Deepak; Murki, Srinivas; Pratap, Tejo (Journal of Nepal Paediatric Society, 2016)
No abstract available. J Nepal Paediatr Soc 2015;35(2):206-207